GE_GERICHTE P/19375/2014 vom 19. September 2014 - GE Cour de justice (2014)
SÉQUESTRE(MESURE PROVISIONNELLE); COMPÉTENCE; SOUPÇON; CONTRAVENTION | CPP.263; CPP.17; CPP.198; CPP.357; LArm.31; LArm.33; LArm.36; CP.103; CP.333; LaCP.11